Identifying Isl1 Genetic Lineage in the Developing Olfactory System and in GnRH-1 Neurons - Taroc, Ed Zandro M.; Katreddi, Raghu Ram; Forni, Paolo E. (Frontiers in Physiology, 2020)
During embryonic development, symmetric ectodermal thickenings (olfactory placodes) give rise to several cell types that comprise the olfactory system, such as those that form the terminal nerve ganglion (TN), gonadotropin releasing hormone-1 (GnRH-1) neurons and other migratory neurons in rodents. Even though the genetic heterogeneity among these cell types are documented, unidentified cell populations arising from the olfactory placode remain. One candidate to identify placodal derived neurons in the developing nasal area is the transcription factor Isl1, which was recently identified in GnRH-3 neurons of the terminal nerve in fish, as well as expression in neurons of the nasal migratory mass. Here, we analyzed the Isl1 genetic lineage in chemosensory neuronal populations in the nasal area and migratory GnRH-1 neurons in mice using in-situ hybridization, immunolabeling a Tamoxifen inducible Isl1CreERT and a constitutive Isl1Cre knock-in mouse lines. In addition, we also performed conditional Isl1 ablation in developing GnRH neurons. We found Isl1 lineage across non sensory cells of the respiratory epithelium and sustentacular cells of OE and VNO. We identified a population of transient embryonic Isl1+ neurons in the olfactory epithelium and sparse Isl1+ neurons in postnatal VNO. Isl1 is expressed in almost all GnRH neurons and in approximately half of the other neuron populations in the Migratory Mass. However, Isl1 conditional ablation alone does not significantly compromise GnRH-1 neuronal migration or GnRH-1 expression, suggesting compensatory mechanisms. Further studies will elucidate the functional and mechanistic role of Isl1 in development of migratory endocrine neurons.